THE INFLUENCE OF LEARNING RESOURCES, LEARNING INTENSITY, AND DISCIPLINE ON LEARNING OUTCOMES OF CLASS XI STUDENTS IN ECONOMICS SUBJECT AT SMA NEGERI JAKARTA SELATAN - Lia Ayu Ashary; Siti Nurjanah; Sri Indah Nikensari (International Journal of Multidisciplinary Research and Literature, 2023)
Study this discussion about influence source study, intensity study, and discipline to results study student class XI on the eye lesson economics at a public high school in South Jakarta. In research, this uses a survey method with an approach quantitative descriptive. The survey method is used to get data for a fact from the place of direct study in a scientific, not artificial, manner. Deep data collection is carried out with method spread questionnaire, interview, and observation in a manner direct without experiment. Descriptive quantitative is a research method that uses data in numbers as a form of subject research to be researched or as a tool for analyzing knowledge that will seek. The subject is student class XI at SMA Negeri Jakarta Selatan, SMAN 38 Jakarta, SMAN 49 Jakarta, and SMAN 109 Jakarta. The study utilized the following research instruments: a form sheet, a questionnaire a variable source. Sheets questionnaire variable intensity study, and sheets questionnaire discipline, whereas variable results study use results Mid Semester Assessment (PTS). The data analysis technique used is analysis multiple linear regression with results equality is Y = 24.551 + 0.085X1 + 0.789X2 + 0.200X3. The study's hypothesis test results show an R square value of 93.3%. F value of 389.567 > 2.713 with a significant 0.000 < 0.05 means that variable source study, intensity study, and discipline together affect positive and significant results study student class XI on the eye lesson economy